EVALUASI STATUS KESUBURAN TANAH DI MASA REPLANTING PERKEBUNAN KELAPA SAWIT PADA TANAH MINERAL PROVINSI JAMBI - Ferry, M; Asmadi Saad; Yulfita Farni (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Appropriate fertilization recommendations are needed to maximize the production of oil palm plants on land that has been used for a long time. This study aimed to determine the status of soil fertility during the oil palm replanting period in Kemang Manis Village, Muara Papalik Sub-district, West Tanjung Jabung Regency, and determine fertilization recommendations according to the needs of oil palm plants based on soil fertility. This study used a survey method; soil samples taken were disturbed soil samples, and sampling was carried out at two depths, namely 0-30 cm and 30-60 cm. Determination of sampling points using stratified random sampling method based on homogeneous land units that were processed based on soil type and slope in the research location. The collected soil samples were analyzed for H, CEC, BS, organic C, P2O5, K2O, and total N. The results showed low fertility status during the oil palm replanting period in the research location. Observations of the soil profile also showed that the O horizon was thin. Fertilization recommendations that must be made to improve soil fertility include adding dolomite fertilizer to increase soil pH value and increasing the availability of N, P, and K elements in the form of Urea, SP36, and KCl. To increase the content of organic materials in the soil, applying oil palm empty fruit bunches can also improve the soil's physical, chemical, and biological properties.